Motor learning outcomes of handrim wheelchair propulsion during active spinal cord injury rehabilitation in comparison with experienced wheelchair users. Issue 10 (8th May 2021) - Leving, Marika T.; de Groot, Sonja; Woldring, Ferry A. B.; Tepper, Marga; Vegter, Riemer J. K.; van der Woude, Lucas H. V.
Abstract: Purpose: To investigate changes in wheelchair propulsion technique and mechanical efficiency across first five weeks of active inpatient spinal cord injury rehabilitation and to compare the outcomes at discharge with experienced wheelchair users with spinal cord injury. Methods: Eight individuals with recent spinal cord injury performed six weekly submaximal exercise tests. The first and last measurement additionally contained a wheelchair circuit and peak graded exercise test. Fifteen experienced individuals performed all above-mentioned tests on one occasion. Results: Mechanical efficiency and propulsion technique did not change during the five weeks of inpatient rehabilitation. Peak power output during peak graded test and performance time on the wheelchair circuit improved between the first and the last week. No difference in propulsion technique, peak power output, and performance time was found between the persons with a recent injury and the experienced group. Mechanical efficiency was higher after the correction for the difference in relative power output in the experienced group. Conclusion: The group with a recent injury did not improve mechanical efficiency and propulsion technique over the period of active rehabilitation, despite significant improvements on the wheelchair circuit and in work capacity. The only significant difference between the groups was found in mechanical efficiency. Implications for rehabilitation: The lack of time-dependent changes in mechanical efficiency and propulsion technique in the group with a recent spinal cord injury, combined with the lack of differences in technique, work capacity and on the wheelchair circuit between the groups, suggest that important adaptations of motor learning may happen even earlier in rehabilitation and emphasize that the group in active rehabilitation was relatively skilled. Standardized observational analyses of handrim wheelchair propulsion abilities during early spinal cord injury rehabilitation provide detailed understanding of wheelchair technique, skill as well as wheelchair propulsion capacity. Measurement of external power output is critical to interpretation of gross efficiency, propulsion technique, and capacity. Wheelchair quality and body weight – next to wheelchair fitness and skill – require careful consideration both in early rehabilitation as well as in the chronic phase of spinal cord injury.